Trait Preference and Performance Evaluation of Indigenous Goat Keepers of Borana Pastoralists in Ethiopia - Mohammed, Hussein; Tesema, Birhanu (Annals of Arid Zone, 2024)
The objectives of this study were to assess the growth and reproductive performance of goats in a pastoral and agropastoral area and Borana-Pastoralists’ preferences for the traits of the indigenous goats. A total of 97 households were interviewed and a total of 194 goats were tracked for six months to collect data. The collected data were analysed using SAS’s GLM and descriptive statistics. The results indicated that pastoralists in the study areas were practicing extensive production systems. The ratio of males to females aged less than six months was proportional. However, females over six months of age outnumbered males proportionally. The overall mean body weight (kg) in the pastoral study area at 0, 90, and 180 days of age were 2.37, 10.5, and 13.8, respectively. Similarly, in agro-pastoral study areas, the result was 2.41, 10.6, and 14.01 kg. The effect of birth type affected the growth of goats with a similar trend and consistently up to weaning was significant (P<0.05). Similarly, the results of the kidding numbers on the growth rate of kids were significantly different (P<0.05). The reproductive performance of goats, age at sexual maturity, age at first kidding, average kidding interval, and duration of reproductive life for the pastoralists’ systems were studied. Accordingly, for the agropastoral area, the corresponding values were 9.70, 10.39, 15.88, 8.27 months, and 8.6 years, respectively, and 9.42, 10.12, 15.78, 8.20, months, and 10.52 years, respectively. The parity effect was significantly different (P<0.05) at 91-180 days of the age of kids on daily weight gain in the study areas. The most preferred traits in both areas were body size, milk yield, and coat color for females as well as body size, coat color, and growth rate for males. Hence, designing goat improvement strategies primarily targets traits towards meet the interest of indigenous goat keepers.